Stress proteins in experimental nephrotoxicity: a ten year experience - Stacchiotti, Alessandra; Bonomini, Francesca; Favero, Gaia; Rossini, Claudia; Rodella, Luigi F.; Rezzani, Rita (Italian Journal of Anatomy and Embryology, 2010)
Heat shock proteins and glucoseregulated proteins represent an extraordinary mechanism of defense induced in the kidney by chemicals or drugs and essential to survive. Here we resume our experience on the presence and regulation of stress proteins into acute and chronic nephrotoxic models in rodents and in vitro. In acute renal damage, induced in rats by a single injection of inorganic mercury, stress proteins enhanced in a dose-dependent manner to recover cytoskeleton and mitochondria and maintain nuclear activity. When we pre-treated mercury injected-rats with antioxidant melatonin or with bimoclomol, a stress proteins-coinducer, stress proteins expression was modulated together with tubular recovery. Similar data were obtained in ischemia-reperfusion in rats treated with stannous chloride, that provided cytoprotection stimulating heme oxygenase induction. During nephrotoxicity induced by administration of cyclosporine A at therapeutic dosage for 1-2 months, stress protein overexpression well correlated with oxidative and cell death, but decreased if we counteracted renal damage using antioxidants. In aluminium intoxication through drinking water for 3-6 months, we detected a time-dependent stress response in the rat kidney that was organ specific and different from the liver. In vitro studies on rat tubular proximal cells exposed to heavy metals demonstrated that stress protein expression was related to peculiar mechanisms of action of each metal. In conclusion, experimental studies on the renal chaperones can greatly contribute to understand their role, and agents able to modulate the stress response might be considered promising therapeutic tools to reduce nephrotoxicity.